Impact of the combined presence of left ventricular systolic and renal dysfunction on the 5-year outcome after ST-elevation myocardial infarction - Savić, Lidija; Mrdović, Igor; Ašanin, Milika; Stanković, Sanja; Matić, Dragan; Krljanac, Gordana; Lasica, Ratko (Vojnosanitetski pregled, 2015)
Background/Aim. The coincidence of left ventricular systolic dysfunction (LVSD) and renal dysfunction (RD) is a strong independent predictor of adverse events in the short-term and mid-term follow-ups of patients with ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (pPCI). The aim of this study was primarily to assess the prognostic impact of the LVSD-RD combination on the 5-year all-cause mortality in patients with STEMI treated with pPCI, as well as to assess the prognostic impact of the LVSD-RD combination on the occurrence of major adverse cardiovascular events (MACEs: cardiovascular death, reinfarction, stroke and target vessel revascularization) in these patients. Methods. We analyzed 951 patients divided into 4 groups according to the presence of LVSD (ejection fraction < 40%) and/or baseline RD (creatinine clearance < 60 mL/min): group I (no LVSD, no RD); group II (LVSD, no RD); group III (RD, no LVSD); group IV (LVSD+RD). Results. The 5-year mortality rates were 2.3%, 17.6%, 11.7% and 38.3%, while the 5-year MACE rates were 8.8%, 28.4%, 18.3% and 44.4% in the groups I, II, III and IV, respectively (p < 0.001). The highest percentage of lethal outcomes and MACE was registered in the first year of follow-up in all the groups. The 1-year landmark analysis confirmed that the patients with LVSD-RD combination had the highest percentage of lethal outcomes in the period of 1 to 5 years (p = 0.028). There was a strong trend toward the significance in the occurrence of MACE among the analyzed groups in the period of 1 to 5 years (p = 0.085). In the Cox regression model the LVSD-RD combination was a strong independent predictor of 5-year mortality and the occurrence of MACE: mortality hazard ratio (HR) 4.5 (95%CI 1.9–10.8); MACE HR 2.5 (95%CI 1.4–4.5). Conclusion. The strong negative independent prognostic impact of the LVSD-RD combination persisted in the long-term follow-up of the patients with STEMI treated with pPCI.
Keywords: myocardial infarction; comorbidity; ventricular dysfunction; left; angioplasty; baloon; mortality; prognosis